Passenger car emissions in urban areas based on local vehicle fleet and environmental conditions - A. Valdés-Montenegro; F.G. Gonzalez-Olivardia; C. Pinzón-Acosta (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: For air quality management, appropriate emission inventories are required to be categorized on-road mobile sources such as cars, depending on their use, vehicle technology, and local environmental conditions. This study aims to estimate atmospheric pollutant emissions generated by passenger cars using the international vehicle emission model for the year 2023.METHODS: To implement the international vehicle emission model and develop a baseline for an emissions inventory, vehicle technology in the study area was identified through surveys at filling fuel stations in the two districts with the highest traffic. The fleet was categorized based on parameters such as emission control technology, fuel type, and engine displacement. Additionally, the study considered geographic and environmental variables, including travel patterns on urban roads, fuel specifications, and elevation.FINDINGS: 53 vehicle categories were identified across the province and classified within the international vehicle emission model. After setting the fleet file with the distribution of vehicle categories and the location file with environmental conditions and representative characteristics, the model estimated atmospheric pollutant emissions for 2023 in metric tons. Passenger cars contributed the most to pollutant emissions, with carbon dioxide reaching 1.78 million tons per year and carbon monoxide 234.16 kiloton per year. Regarding emission factors, gasoline vehicles showed a proportional increase in carbon dioxide, nitrous oxide, nitrogen oxides, and sulfur oxides emissions per kilometer as vehicle size increased. A notable case was carbon monoxide emissions, where a medium-sized vehicle emitted approximately 41 grams per kilometer—twice the amount of a heavy car as 23 grams per kilometer, according to international vehicle emission model estimation. Particulate matter emissions were primarily generated by heavy passenger vehicles, compared with light and medium cars, whose emissions were 90 percent and 83 percent, respectively.CONCLUSION: This study developed an on-road mobile source emission inventory for 2023, focusing on passenger cars in Panama. A survey of 409 vehicles characterized a fleet of 534,322 cars, identifying 53 categories, with 94.8 percent running on gasoline and 5.12 percent on diesel. More than 45 percent of the vehicles exceed 160,000 kilometers, increasing their emissions. Medium-sized cars (1.5–3 liters) account for 61.1 percent of the fleet and are the largest emitters of carbon dioxide and nitrogen oxide. Although fewer in number, diesel vehicles produce nearly half of the particulate matter-10 emissions. Comparisons with national and international inventories validate the contribution of these vehicles to air pollution and the impact of each pollutant.